Steady change: the 200 largest US manufacturing firms throughout the 20th century - Louçã, F.; Mendonça, S. (Industrial and Corporate Change, 2002)
This paper discusses the existence of structural change in business activity and technological competence among the 200 largest US manufacturing companies throughout the 20th century. The data were taken from Chandler (Scale and Scope, 1990) and Fortune magazine. The analysis of corporate evolution in used to assess continuity versus turbulence of business organizations in the context of the neo?Schumpeterian long?wave hypothesis. The empirical results show that the giants of the late 20th century are not the same as those at the beginning of that period. Persistence in the sample is very limited. Moreover, turbulence is not smooth, but rather occurs by impulses that affect specific industries, and it has increased over time. Overall, the pattern of corporate entry and industry development is very indicative of the new opportunities emerging with information and communication technologies. This process of open?ended continuous transformation supports the case for putting change at the centre of economic analysis.